Techno-Economic Analysis of Biogas Production from Cow Manure - Muharja, Maktum; Khotimah, Husnul; Rizki Fitria , Darmayanti; Andika, Prastika; Achri Isnan, Khamil; Badril, Azhar (Jurnal Teknik Kimia dan Lingkungan, 2024)
Biogas has been considered as a renewable alternative energy produced by anaerobic digestion of cow manure. A process of anaerobic digestion of cow manure was simulated by Aspen Plus software to analyze the cost of production. The simulated project used cow manure wastes as a feedstock. From the study, economic analysis includes Net Present Value (NPV), Internal Rate of Return (IRR), Payback period (PBP), and B/C Ratio. The resulting BEP value is 539.20, the NPV is 6,414,566,421.98, the IRR is 249.84%, and the B/C ratio is 1.66. These values can be said that the business of cow dung which is processed into biogas is feasible to run.